Job Pierson family papers - Pierson, Job, 1791-1860.; Pierson, Job, 1824-1896.
Chiefly letters (1831-1835) written by Job Pierson (1791-1860) to his wife, Clarissa Bulkeley Pierson, while serving in Congress describing life in Washington, D.C., during the administration of Andrew Jackson; journal (1843) and typewritten transcripts of diary entries (1849-1896) of Job Pierson (1824-1896) relating to his studies at Williams College, his religious conversion, family life, and his career as a Presbyterian clergyman in New York and Michigan; legal and financial papers (1755-1886) relating to the family's properties in Rensselaer and Suffolk counties, N.Y.; scrapbook compiled in 1908 by Philip T. H. Pierson in memory of his brother, Bowen Whiting Pierson, containing family photographs and genealogical material; and other Pierson (Pearson) family papers.
Job Pierson (1791-1860) was a lawyer in Albany and a U.S. representative from New York. His son, Job Pierson (1824-1896), was a Presbyterian clergyman in New York and Michigan and later librarian at Alma College, Alma, Mich.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Jackson, Andrew, -- 1767-1845.; Pearson family; Pierson, Bowen Whiting; Pierson, Clarissa Bulkeley; Pierson, Philip T. H; Williams College -- Students; Conversion -- Christianity; Presbyterian Church -- Michigan -- Clergy; Presbyterian Church -- New York (State) -- Clergy; Real property -- New York (State) -- Rensselaer County; Real property -- New York (State) -- Suffolk County; New York (State) -- Politics and government; United States -- Politics and government -- 1829-1837.; Washington (D.C.) -- Social life and customs -- 19th century; Clergy; Lawyers; Representatives, U.S. Congress -- New York (State)